The Dynamics of Poverty in Vietnam: An Adjusted Categorization and the Multinomial Logit Regression Approach - Lê Thỵ Hà Vân (My University, 2022)
The Dynamics of Poverty in Vietnam: An Adjusted Categorization and the Multinomial Logit Regression Approach
Keywords: Poverty dynamics; Logit regression; Vietnam poverty